Pain assessment and management in the NICU: analysis of an educational intervention for health professionals - Carmen L.G. de Aymar; Luciane S. de Lima; Cândida M.R. dos Santos; Emilly A.C. Moreno; Sônia B. Coutinho (Jornal de Pediatria (Versão em Português), 2014)
Objective: to study the perception of a Neonatal Intensive Care team on pain assessment and management before and after an educational intervention created and implemented in the unit. Methods: intervention study developed as action research, in three phases. In Phase 1, a quantitative study was performed to identify how professionals perceive pain management in the unit. In Phase 2, an educational intervention was carried out, using the Operational Group (OG), which defined strategies to be adopted to seek improvements in pain assessment and management. In Phase 3, the initial questionnaire was reapplied to assess professionals’ perceptions about the subject after the intervention. All professionals directly working in newborn care were included. Results: the perception of professionals about pain management and assessment in the unit showed a statistically significant difference between the two phases of research, highlighting the increase in frequency of reference for evaluation and use of some method of pain relief procedures for most analyzed procedures. Participation in training (one of the strategies defined by the operational group) was reported by 86.4% of the professionals. They reported the use of scales for pain assessment, established by the protocol adopted in the service after the intervention, with a frequency of 94.4%. Changes in pain assessment and management were perceived by 79.6% of the participants. Conclusion: the professionals involved in the educational intervention observed changes in pain management in the unit and related them to the strategies defined and implemented by the OG.